A unique cross section through the skin of the dinosaur Psittacosaurus from China showing a complex fibre architecture - Lingham-Soliar, Theagarten (The Royal Society, 2008)
This paper reports on a unique preservation of soft tissues in the ventrolateral region of the plant-eating dinosaur Psittacosaurus from the Jehol biota of China. The preservation is of a deep cross section through the dermis, which includes multiple layers of collagenous fibres in excess of 25, among the highest recorded in vertebrates, with a further 15 more layers (poorly preserved) estimated for the entire height of the section. Also, for the first time in a dinosaur two fibre layers parallel to the skin surface are preserved deep within the dermis at the base of the cross section. These fibre layers comprise regularly disposed fibres arranged in left- and right-handed geodesic helices, matching the pattern at the surface and reasonably inferred for the entire section. As noted from the studies on modern-day animals, this fibre structure plays a critical part in the stresses and strains the skin may be subjected to and is ideally suited to providing support and protection. Psittacosaurus gives a remarkable, unprecedented understanding of the dinosaur skin.